DEVELOPMENTAL GUIDELINES FOR RELIGIOUS TOURISM, BETONG SUB-DISTRICT, YALA PROVINCE - Laeheem, Kasetchai; Chitwiboon, Pongtach; Tepsing, Punya; Boonwanno, Sakawrat; Yeetin, Poranee (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This study is qualitative research. It aims to study religious tourist attractions and study developmental guidelines for religious tourism in Betong Sub-district, Yala Province. Phenomenology was used, and data was collected from documents and fieldwork by observation, in-depth interviews as well as group discussion. Key informants were 6 tourism officials, 6 private entrepreneurs, 6 community leaders, 5 tourists, and 5 of those who were related to religious tourism, a total of 28 key informants. The result revealed that religious tourist attractions in Betong Sub-district, Yala Province was famous for tourists and can be connected to religious tourism route in the future. It was comprised of Wat Phothisatto Chaomae Kuan Im, Wat Phuttha Thiwat, and Betong Sub-district Foundation. Each attraction contained unique historical narratives and religious tourism activities such as celebration of Wat Phothisatto Chaomae Kuan Im, candlelight procession, fortune teller and lottery teller. The developmental guidelines for religious tourism in Betong Sub-district, Yala Province consisted of 6 suggestions which could be grouped to form the core of religious tourism development in 4 dimensions 1) Planning such as capability of tourism program; 2) Management such as capability of access to the activities; 3) Supervision such as services of tourist attractions and facilities; and 4) Coordination such as attractions. Consequently, governmental organizations should lead for the coordination and empowerment of synergy of working together as well as aware of the value of each religious tourist attraction. Finally, these guidelines would result in the future strengthening of the economic and social tourism community of Betong.